Odpowiedzi

Najlepsza Odpowiedź!
2010-03-14T18:37:28+01:00
A) - 3x = 2x - 10
-3x-2x = -10
-5x = -10 / :(-5)
x = 2

b) 2x - 2 = 7 - x
2x+x = 7+2
3x = 9 / : 3
x = 3

c) 10 = 4 - 2x
2x = 4-10
2x = -6 / : 2
x = -3

d) -(2x-1) = 4
-2x+1 = 4
-2x = 4-1
-2x = 3 / : (-2)
x = - ³/₂
x = -1 ½

e) 2(x+1) = x
2x+2 = x
2x-x = -2
x = -2

f) 2t - (3t+1) = 6
2t - 3t-1 = 6
2t-3t = 6+1
-t = 7 / :(-1)
t = -7
11 4 11
2010-03-14T18:39:45+01:00
A.x=2
b.x=3
c.x=3
d.x=1,5
e.x=-2
f.t=7
3 2 3
2010-03-14T18:40:46+01:00
A)- 3x = 2x - 10

10=2x+3x
10=5x/;5
x=2
b)2x - 2 = 7 - x
2x+x=7+2
3x=9/;3
x=3
c)10 = 4 - 2x
10-4=2x
6=2x/;2
x=3
d)-(2x-1) = 4
-2x+1=4
-2x=4-1
-2x=3/;-2
x=-1,5

e) 2(x+1) = x
2x+1=x
2x-x=-1
x=-1
f)2t - (3t+1) = 6
6t(kwadrat)-2t=6
4t=6/;4
x=1,5
1 2 1